2009
DOI: 10.1016/j.epsl.2009.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Flux and size fractionation of 3He in interplanetary dust from Antarctic ice core samples

Abstract: Accretion of extraterrestrial material to earth is of interest for a variety of reasons, including as a possible driver of long or short-term climate change, and as a record of solar system events preserved in the geological record. hypothesis that helium in IDPs is primarily solar helium implanted in particle surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Only small particles which effectively re-radiate heat, or rare larger particles on unusually low velocity trajectories, arrive on the Earth's surface with their He intact. Modeling suggests that most 3 He-bearing IDPs penetrating the atmosphere are smaller than about 30 lm (Farley et al, 1997), a result confirmed by a few direct measurements (Mukhopadhyay and Farley, 2006;Brook et al, 2009;McGee et al, 2010). While meteorite fragmentation has been proposed as an important source of the extraterrestrial 3 He flux (Lal and Jull, 2005), this possibility has been refuted (Brook et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Only small particles which effectively re-radiate heat, or rare larger particles on unusually low velocity trajectories, arrive on the Earth's surface with their He intact. Modeling suggests that most 3 He-bearing IDPs penetrating the atmosphere are smaller than about 30 lm (Farley et al, 1997), a result confirmed by a few direct measurements (Mukhopadhyay and Farley, 2006;Brook et al, 2009;McGee et al, 2010). While meteorite fragmentation has been proposed as an important source of the extraterrestrial 3 He flux (Lal and Jull, 2005), this possibility has been refuted (Brook et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…(2) noble gas retentivity (as proposed by Mukhopadhyay and Farley (2006)); and (3) presence of grain sizes <10 lm (Mukhopadhyay and Farley, 2006;Brook et al, 2009). Additional, anecdotal evidence includes the presence of dendritic grains consistent with stoichiometric ilmenite and ulvospinels.…”
Section: 'Normal' Background Samplementioning
confidence: 89%
“…Fukumoto et al, 1986;Hiyagon, 1994). Recent studies suggest >60% of retained 3 He resides in the <37 lm particle fraction, while approximately half is within particles between 5 and 13 lm (Mukhopadhyay and Farley, 2006;Brook et al, 2009).…”
Section: Idp's and Noble Gas Accumulation On Earthmentioning
confidence: 97%
See 1 more Smart Citation
“…A major drawback to most of these tracers is that they require relatively large volumes and stratigraphic thicknesses of ice. For example, a study of extraterrestrial He 3 abundance in replicate samples found that around 1000 g of ice were needed to achieve reproducible results with 2σ errors on the order of ±30% (Brook et al, 2009). Another study achieved lower errors, but individual samples represented over 100 yr of ice accumulation (Winckler and Fischer, 2006).…”
Section: Previous Work On Extraterrestrial Debris Within Polar Icementioning
confidence: 99%